Subjective Knowledge and AI Privacy Risks - Paalimäki, Mari; Munnukka, Juha (39th Bled eConference: Co-Creating Human-Centred and Responsible Digital Futures; Conference Proceedings, 2026)
Artificial Intelligence (AI) systems are increasingly used in everyday decision-making, but the adaptive and opaque nature makes them difficult to understand, creating uncertainty in evaluating risks. Prior research has examined privacy risk through factors such as trust and perceived control but lacks an explanatory mechanism for how individuals assess such risk in AI context. This study explores the role of subjective knowledge, defined as individuals' perceived understanding of a system, in shaping privacy risk perception using a pilot experiment with two modalities (text vs. voice). The results suggest that subjective knowledge is associated with privacy risk perception and usage intention, providing preliminary insight of the underlying mechanism and highlighting its importance in AI-based interaction.